A rare case of giant condyloma acuminata during pregnancy - Choudhary, Neeraj; Verma, Savitri; Gandhi, Sudha; Sharma, Anuj Kumar; Kumari, Asha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Genital warts (Condyloma acuminata) are a benign lesion caused by human papillomavirus (HPV) type-6 or type-11 and are usually transmitted sexually. During pregnancy, condyloma has a tendency to proliferate and may have recurrence. We have a case of G2P1L1 38 weeks previously normal vaginal delivered patient in our hospital with extensive genital warts. Patient was successfully managed by surgical excision and after that in follow up after 2 months for podophyllin resin application on remaining lesions. HPV infection presentation can range from asymptomatic to cervical cancer. Small genital wart lesion may become extensive and cumbersome during pregnancy and again regress after delivery in due course of time. HPV vaccination, sex education and early treatment of condyloma lesions should prevent and, in any case, improve the prognosis of this disease.